The reflection of psychological sports preparation on the performance of football players-senior- - DERRADJI, Abbes; NETTAH, Kamel (sports creativity, 2024)
Our study aims at highlighting the importance of psychological sports preparation in improving the performance of football players as well as in achieving satisfactory results, and to identify how the process of psychological preparation affects the level of performance of football players. in addition, It sheds light on the reality of this important process at the level of amateur clubs in the state of Bouira .To reach a result In this study, we relied on the descriptive approach, by submitting questionnaire forms to our research sample that were randomly selected to represent football players and coaches. After collecting the data and the results obtained, we ‘ve reached a conclusion that psychological preparation for sports has very positive repercussions on the performance of football players Through its contribution to confronting some of the disturbances that players may face during competition. It also contributes to developing some psychological skills, such as self-confidence, developing motivation, and increasing concentration, which are directly related to their performance due to the negative emotions that affect most players before competition.